2x+7=-x+1

Simple and best practice solution for 2x+7=-x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7=-x+1 equation:


Simplifying
2x + 7 = -1x + 1

Reorder the terms:
7 + 2x = -1x + 1

Reorder the terms:
7 + 2x = 1 + -1x

Solving
7 + 2x = 1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
7 + 2x + x = 1 + -1x + x

Combine like terms: 2x + x = 3x
7 + 3x = 1 + -1x + x

Combine like terms: -1x + x = 0
7 + 3x = 1 + 0
7 + 3x = 1

Add '-7' to each side of the equation.
7 + -7 + 3x = 1 + -7

Combine like terms: 7 + -7 = 0
0 + 3x = 1 + -7
3x = 1 + -7

Combine like terms: 1 + -7 = -6
3x = -6

Divide each side by '3'.
x = -2

Simplifying
x = -2

See similar equations:

| 4-3/7 | | 4(3x+7)=25 | | 2/4*=6 | | 11x-2=53 | | f(x)=8(cos(x)) | | 2/3P=40 | | 4c^2-100=0 | | 5m-2=7 | | -2*x=20 | | 2a-2b-3c=12.5 | | 5x+3x=19 | | 4/2y=8 | | 0=x^3-6x^2+9x+15 | | 2x-1+2x+1+x=180 | | f(0)=x^3-6x^2+9x+15 | | 5+11=16 | | 4=22-9x | | 5+11= | | x^2+28x=-192 | | f(x)=x^3-6x^2+9x+15 | | 12-(7-x)=45 | | y=-2x^2+12x-14 | | f(x)=5xln(9x)-5x | | 21+4(9-5)= | | x=0.95(x+y) | | -18-1+25+36=-3-4m-6+5m | | 42*22= | | 4x-5+7=2x+8 | | 1+4(x+7)=-19 | | (42)3.14= | | 2*3.28571429-10/7= | | (s)(-3st)(.3)= |

Equations solver categories